Examining Science Self-Efficacy in Basic Science Learning Among Generation Z Pre-Service Elementary School Teachers - Siti Zahra Mulianti Natsir; Sitti Hajar (JGK (Jurnal Guru Kita), 2026)
Science self-efficacy plays an important role in shaping pre-service teachers’ confidence, persistence, and ability to teach science effectively. This study aimed to examine the science self-efficacy of Generation Z pre-service elementary school teachers in Basic Science learning. A mixed-methods design was employed involving 122 students from the Elementary School Teacher Education Program (PGSD). Quantitative data were collected using an 18-item self-efficacy questionnaire based on the dimensions of magnitude, generality, and strength, while qualitative data were obtained through open-ended questions. The instrument was declared valid with Corrected Item-Total Correlation (CITC) values ranging from 0.468 to 0.781 and reliable with a Cronbach’s Alpha coefficient of 0.760. Quantitative findings showed that students had a high level of self-efficacy, with an overall mean score of 4.07. The strength domain obtained the highest score, indicating strong persistence and resilience in learning science. Qualitative findings revealed that students experienced difficulties in understanding abstract concepts, calculation-based materials, and practicum reports. To overcome these challenges, students commonly used strategies such as reviewing materials, peer discussion, searching for additional resources, and utilizing digital platforms and AI tools. The findings suggest that cognitive, social, and affective factors collectively influence Gen-Z students’ science self-efficacy.